Sosialisasi Sistem Penerangan Listrik dan Perhitungan Tarif Listrik Tahun 2020 pada Pemuda Muhammadiyah Cabang Pulo Brayan Darat - Abdullah Abdullah; Cholish Cholish; Moh. Zainul Haq; Ferdinan Rinaldo Tampubolon; Rischa Devita (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The increasing use of electrical energy in society in 2020 is closely related to the pandemic problem that is occurring. Increased household activity causes a surge in energy in the household sector. This increase in energy consumption needs to be balanced by providing exposure to the utilization of existing electrical equipment in households. The lighting system give an important role in energy consumption in the household sector. The dedication carried out is by providing knowledge on the use of the lighting system, the rules in PUIL 2000 and the calculation of the Basic Electricity Tariff (TDL) in 2020. Submission of this will certainly increase public understanding of energy savings so that it can contribute to overcoming the problem of electricity devisit occur.